Mengemis Sebagai Profesi (Tinjauan Hukum Islam pada Masyarakat stren Kali Jagir kecamatan Wonokromo Kota Surabaya) - Agung Firmansyah (Universitas Muhammadiyah Surabaya, 2013)
Abstract Vagrants and beggars are problems that continuouslybecome government's attention. In accordance with the regulation (UU). This program is a social rehabilitation program for vagrants and beggars which integrated based on rural area emphasizing to return them to their hometown or re-migration. Various solutions and policies tried to do by the government, but as if the solutions and policies do not really give an optimal impact due to the fact that the number of beggars has increased. This research aims to determine the factors that make people make the profession of begging as a source of revenue without going to seek better job.This research is a field research in Islamic law that having characteristics of descriptive qualitative. In collecting the data, the researcher used observation and interview techniques.The data analyzed qualitatively based on the theory related to the researchobject, and the subject of this research was 30 beggars which is consists of 15 men, 15 women and six others were children. From these research obtained that the beggars in Jagirriverbank of Wonokromo subdistrict largely dominated by adults and children, with some of the characteristics background as followed: 1). They are lazy to work and would rather to beg. In other words they do not have the expectation or hope to live strongly. 2). The lack of discipline from parents or guardians who could be as a role models or examples, but mistakes in educating, so there were exploitation of early childhood. 3). They were tempted to livelihood in a city which is considered pledged so that create urbanization to town without any preparation or expertise. Beggars in Jagir riverbank of Wonokromo Surabaya is none other than as a profession that is prohibited by religion. Islam is not ordained by begging, lying or deceiving. The reason is not only because it violates the sin, but also because such actions are deemed contaminate good deeds and depriving the poor people who do need help, even it ruin the good image of the poor people who do not want to beg and those who love virtue. Keywords: Begging, Profession, and Stren